2011
DOI: 10.1299/jsdd.5.155
|View full text |Cite
|
Sign up to set email alerts
|

Active Vibration Control of an Elevator Car Using Two Rotary Actuators

Abstract: A new control device is proposed to isolate an elevator cabin from irregularities on a guide rail. The device consists of two rotary electric motors with disks and eccentric masses. One motor produces torque to rotate the eccentric mass according to the command signals from the controller for horizontal control, while the other rotates the mass to eliminate the unwanted vertical force. To design the optimal controller to reduce the horizontal vibration of the cabin, the dynamics of the cabin, including the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The traditional methods usually reduce the horizontal vibration of a car by improving the manufacturing and installation accuracy of mechanical parts and adding damping elements. Nakano et al (2011) proposed a novel damping element that consisted of two rotating motors and one eccentric disc. The experimental results showed that the damper could effectively reduce the horizontal vibration without generating unnecessary vertical force.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional methods usually reduce the horizontal vibration of a car by improving the manufacturing and installation accuracy of mechanical parts and adding damping elements. Nakano et al (2011) proposed a novel damping element that consisted of two rotating motors and one eccentric disc. The experimental results showed that the damper could effectively reduce the horizontal vibration without generating unnecessary vertical force.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 At present, control methods for elevator horizontal vibration reduction include passive vibration reduction 3 and active control. 4,5 Guide shoe spring and rubber block are often used to isolate the car system in passive vibration reduction. The damping force provided by this method is small, which is difficult to meet riding comfort requirements of ultra-high-speed elevator.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of control algorithms, Nakano et al [14] used the acceleration response of the car system as the control objective and applied the optimal feedback control method to control the horizontal vibration acceleration of the car, thus achieving suppression of the horizontal vibration of the car system. Naoaki et al [15] used the H ∞ control method to design a robust controller for the horizontal vibration of the car system.…”
Section: Introductionmentioning
confidence: 99%